Heidegger’s forgetfulness: about aion and initial words - Maureira Velásquez, Marco (Logos. Anales del Seminario de Metafísica, 2021)
Widely known is the confrontation that Heidegger maintains with Nietzsche’s thought, vindicating the question of the meaning of Being in relation to his vitalist problematization. Also known are the later philosophical proposals that denounce being-toward-death, recreating new problematizations in which Life plays a leading role, taking untimely revenge against the Dasein. However, these proposals are usually executed from an external problematization that is alien to Heidegger’s own way of thinking. In this work, on the contrary, a frame of mind will be adopted in accordance with the Heideggerian question that, listening to the initial words of the thinkers of the beginning, problematizes the hierarchical relations established between Being and Life.